Calcium imaging reveals a network of intrinsically light-sensitive inner-retinal neurons. - Sekaran, S; Foster, R; Lucas, R; Hankins, M (2003)
BACKGROUND: Mice lacking rod and cone photoreceptors (rd/rd cl) are still able to regulate a range of responses to light, including circadian photoentrainment, the pupillary light reflex, and suppression of pineal melatonin by light. These data are consistent with the presence of a novel inner-retinal photoreceptor mediating non-image-forming irradiance detection. RESULTS: We have examined the nature and extent of intrinsic light sensitivity in rd/rd cl retinae by monitoring the effect of light stimulation (470 nm) on intracellular Ca(2+) via FURA-2 imaging. Using this approach, which does not rely on pharmacological or surgical isolation of ganglion cells from the rod and cone photoreceptors, we identified a population of light-sensitive neurons in the ganglion cell layer (GCL). Retinal illumination induced an increase of intracellular Ca(2+) in approximately 2.7% of the neurons. The light-evoked Ca(2+) fluxes were dependent on the intensity and duration of the light stimulus. The light-responsive units formed an extensive network that could be uncoupled by application of the gap junction blocker carbenoxolone. Three types of light-evoked Ca(2+) influx were observed: sustained, transient, and repetitive, which are suggestive of distinct functional classes of GCL photoreceptors. CONCLUSIONS: Collectively, our data reveal a heterogeneous syncytium of intrinsically photosensitive neurons in the GCL coupled to a secondary population of light-driven cells, in the absence of rod and cone inputs.